Logistic regression modelling at insurance interest: Theory of planned behavior - Hakim, Lukmanul; Santoso, Agus (Desimal: Jurnal Matematika, 2023)
One of the characteristics of people who have good financial literacy is having good risk management skills. This study aims to make logistic regression modeling of risk management or insurance interests from Sumbawa University of Technology lecturers. This research uses quantitative methods by combining mathematical theory, statistics, and management science (Theory of Planned Behavior). This research uses primary data from Sumbawa University of Technology as samples. From the data collected using the probability sampling method, it was found that of the four variables (literacy as X_1, inclusion as X_2, family as X_3, gender as D_1, and insurance interest as Y) used, only the family variable had a significant impact on increasing someone's interest in insurance (opportunity). The exponential values of the four variables are: X_1= 3.230 means 1 unit in the literacy variable will have an impact on the possibility of increasing interest in insurance by 3.230 times, X_2= 0.548 means 1 unit in the inclusion variable will have an impact on the possibility of increasing interest in insurance by 0.548 times, X_3=3.886 means 1 unit in the family variable will have an impact on the possibility of increasing interest in insurance by 3.886 times, and D_1=0.813 means the male gender has an impact 0.813 times greater than the female sex on increasing interest in insurance.